All-solid-state battery

By setting a negative electrode intermediate layer containing metal material and carbon material between the negative electrode current collector of the lithium precipitation all-solid state battery and the solid electrolyte layer, and controlling its porosity, the problem of pores in the charging process of the lithium precipitation all-solid state battery is solved, and the charging performance and cycling durability of the battery are significantly improved.

CN120113078APending Publication Date: 2025-06-06NISSAN MOTOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380074947.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-27
Filing Date
2023-09-26
Publication Date
2025-06-06

AI Technical Summary

Technical Problem

Lithium-precipitation all-solid-state secondary batteries may generate pores during charging, resulting in a decrease in discharge capacity, and insufficient resistance, cycle characteristics and short-circuit rate during charging.

Method used

A negative electrode intermediate layer containing a metal material that can alloy with lithium or a carbon material that can absorb lithium ions and contains a binder is arranged between the negative electrode current collector and the solid electrolyte layer, and the porosity thereof is controlled to be 10% or more and 70% or less.

Benefits of technology

With this structure, the charging resistance, cycle characteristics and charging short-circuit rate of lithium-precipitation all-solid-state batteries can be significantly improved, and the service life of the battery can be extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120113078A_ABST
    Figure CN120113078A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide an all-solid-state battery of a lithium deposition type, the all-solid-state battery having excellent resistance during charging, cycle characteristics, and short-circuit rate during charging. Provided is an all-solid-state battery provided with a power generation element having: a positive electrode having a positive electrode active material layer containing a positive electrode active material; a negative electrode which has a negative electrode current collector and in which lithium metal is deposited on the negative electrode current collector during charging; a solid electrolyte layer that is interposed between the positive electrode and the negative electrode and contains a solid electrolyte; and a negative electrode intermediate layer that is present adjacent to the negative electrode collector-side surface of the solid electrolyte layer and contains a binder and at least one material selected from the group consisting of a metal material that can be alloyed with lithium and a carbon material that can absorb lithium ions, the negative electrode intermediate layer having a porosity of 10-70% inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an all-solid-state battery. Background Art

[0002] In recent years, research and development of all-solid-state batteries using oxide-based and sulfide-based solid electrolytes in electrolytes has become popular. Solid electrolytes are materials mainly composed of ion conductors that can conduct ions in solids. Therefore, in all-solid-state batteries, there is an advantage that in principle, various problems caused by flammable organic electrolytes, as in the previous liquid batteries using non-aqueous electrolytes, will not occur.

[0003] As one kind of all-solid-state secondary battery, it is known that the so-called lithium precipitation type all-solid-state secondary battery in which lithium metal is precipitated on the negative electrode collector during charging. It is known that in such a lithium precipitation type all-solid-state secondary battery, the lithium metal precipitated during charging is ionized during discharge, thereby generating pores in the lithium metal, which may become the reason for reducing the discharge capacity. Therefore, in order to suppress the generation of such pores, in the lithium precipitation type all-solid-state secondary battery, a constraint pressure is usually given in the stacking direction of the battery.

[0004] As a means of suppressing the generation of pores associated with discharge without applying high restraint pressure, Japanese Patent Gazette No. 2020-191202 discloses a technique of providing a negative electrode active material layer (negative electrode intermediate layer) containing Ag between the negative electrode collector and the solid electrolyte layer. By setting such a configuration, Li is precipitated in the form of a Li(Ag) alloy in which Ag is solid-dissolved during the charging process. Moreover, during the discharge process, only Li dissolves from the Li(Ag) alloy, and the solid-dissolved Ag remains, so the generation of pores can be suppressed. Summary of the invention

[0005] However, the inventors of the present invention have conducted research and found that even the lithium precipitation-type all-solid-state battery with a negative electrode intermediate layer described in Japanese Patent Application Publication No. 2020-191202 sometimes has insufficient resistance during charging, cycle characteristics, or short-circuit rate during charging.

[0006] Therefore, an object of the present invention is to provide, among lithium deposition type all-solid-state batteries, an all-solid-state battery having excellent resistance during charging, cycle characteristics, and short-circuit rate during charging.

[0007] The present inventors have conducted in-depth research to solve the above problems. As a result, it is found that in an all-solid-state battery with a lithium-precipitated power generation element, a negative electrode intermediate layer including a metal material capable of alloying with lithium or a carbon material capable of absorbing lithium ions and a binder is provided between the negative electrode collector and the solid electrolyte layer, and the porosity of the negative electrode intermediate layer is controlled within a specific range, so that the above problems can be solved, thereby completing the present invention.

[0008] That is, one embodiment of the present invention is an all-solid-state battery, which has a power generation element, and the power generation element has: a positive electrode, which has a positive electrode active material layer containing a positive electrode active material; a negative electrode, which has a negative electrode collector, and lithium metal is precipitated on the negative electrode collector during charging; a solid electrolyte layer, which is between the positive electrode and the negative electrode and contains a solid electrolyte; and a negative electrode intermediate layer, which exists adjacent to the surface of the negative electrode collector side of the solid electrolyte layer, contains at least one selected from the group consisting of a metal material capable of alloying with lithium and a carbon material capable of absorbing lithium ions and a binder, and the porosity of the negative electrode intermediate layer is greater than 10% and less than 70%. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] [ Figure 1 ] Figure 1 It is a cross-sectional view schematically showing the entire structure of a stacked-type (internal parallel connection type) all-solid lithium secondary battery (stacked-type secondary battery) as one embodiment of the present invention. DETAILED DESCRIPTION

[0010] One embodiment of the present invention is an all-solid-state battery, which has a power generation element, wherein the power generation element has: a positive electrode having a positive electrode active material layer containing a positive electrode active material; a negative electrode having a negative electrode collector, on which lithium metal is precipitated during charging; a solid electrolyte layer, which is between the positive electrode and the negative electrode and contains a solid electrolyte; and a negative electrode intermediate layer, which exists adjacent to the surface of the negative electrode collector side of the solid electrolyte layer, and contains at least one selected from the group consisting of a metal material capable of alloying with lithium and a carbon material capable of absorbing lithium ions and a binder, wherein the porosity of the negative electrode intermediate layer is greater than or equal to 10% and less than or equal to 70%. According to the all-solid-state battery of this embodiment, in a lithium precipitation type all-solid-state battery, an all-solid-state battery having excellent resistance during charging, cycle characteristics, and short circuit rate during charging can be provided.

[0011] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. It should be noted that in the description of the accompanying drawings, the same elements are marked with the same reference numerals, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are exaggerated for the convenience of description and are sometimes different from the actual ratios.

[0012] Figure 1 This is a cross-sectional view schematically showing the overall structure of a stacked type (internal parallel connection type) all-solid-state lithium secondary battery (hereinafter also referred to as a "stacked type secondary battery") as one embodiment of the present invention. It should be noted that, Figure 1 The cross section of the stacked secondary battery during charging is shown. Figure 1 The stacked secondary battery 10a shown has a structure in which a roughly rectangular power generation element 21 that actually performs charge and discharge reactions is sealed inside a laminate film 29 that serves as a battery outer casing. Here, the power generation element 21 has a structure in which a negative electrode, a solid electrolyte layer 17, and a positive electrode are stacked. The negative electrode has a structure in which a negative electrode collector 11' and a negative electrode active material layer 13 formed of lithium metal precipitated on the surface of the negative electrode collector 11' are stacked. In addition, a negative electrode intermediate layer 14 is arranged adjacent to the surface of the negative electrode active material layer 13 that is opposite to the solid electrolyte layer 17. The positive electrode has a structure in which a positive electrode active material layer 15 is arranged on the surface of the positive electrode collector 11". In addition, the negative electrode, the solid electrolyte layer, and the positive electrode are stacked in sequence in a manner in which the negative electrode intermediate layer 14 and the positive electrode active material layer 15 are opposite to each other with the solid electrolyte layer 17 interposed therebetween. Thus, the adjacent negative electrode, solid electrolyte layer, and positive electrode constitute a single battery layer 19. Therefore, Figure 1 The stacked secondary battery 10a shown can be said to have a structure electrically connected in parallel by stacking a plurality of single battery layers 19. It has the following structure: a negative electrode collector plate 25 and a positive electrode collector plate 27 which are electrically connected to each electrode (negative electrode and positive electrode) are respectively mounted on the negative electrode collector 11' and the positive electrode collector 11", and are led out to the outside of the laminated film 29 in a manner of being clamped at the end of the laminated film 29. A constraining pressure is applied to the stacked secondary battery 10a in the stacking direction of the power generation element 21 by a pressurizing component (not shown). Therefore, the volume of the power generation element 21 remains constant.

[0013] Hereinafter, main components of the all-solid-state battery of this embodiment will be described.

[0014] [Current Collector]

[0015] The current collector (negative electrode current collector, positive electrode current collector) has the function of mediating the movement of electrons from the electrode active material layer (negative electrode active material layer, positive electrode active material layer). There is no particular restriction on the material constituting the current collector. As the constituent material of the current collector, for example, metals such as aluminum, nickel, iron, stainless steel, titanium, copper, and conductive resins can be used. There is no particular restriction on the thickness of the current collector, and as an example, it is 10 μm to 100 μm.

[0016] [Negative Electrode Active Material Layer]

[0017] The all-solid-state battery of this method is a so-called lithium precipitation type all-solid-state battery in which lithium metal is precipitated on the negative electrode collector during the charging process. The layer formed by the lithium metal precipitated on the negative electrode collector during the charging process is the negative electrode active material layer of the all-solid-state battery of this method. Therefore, as the charging process proceeds, the thickness of the negative electrode active material layer increases, and as the discharge process proceeds, the thickness of the negative electrode active material layer decreases. The negative electrode active material layer may not exist during full discharge, but depending on the circumstances, a certain degree of negative electrode active material layer formed by lithium metal may be configured during full discharge. In addition, there is no particular restriction on the thickness of the negative electrode active material layer (lithium metal layer) during full charge, which is usually 0.1 to 1000 μm.

[0018] [Negative electrode intermediate layer]

[0019] The negative electrode intermediate layer is a layer adjacent to the negative electrode collector side of the solid electrolyte layer, and contains at least one selected from the group consisting of a metal material capable of alloying with lithium and a carbon material capable of absorbing lithium ions, and a binder. It should be noted that the negative electrode intermediate layer is preferably conductive as a whole. The volume resistivity of the negative electrode intermediate layer is not particularly limited, and is preferably 10 2 Ω·cm or less, more preferably 10 Ω·cm or less. In the present specification, the volume resistivity of the negative electrode intermediate layer is a value measured using an electrode resistance measurement system (manufactured by HIOKI Electric Co., Ltd., product name: RM2610).

[0020] The negative electrode intermediate layer preferably contains at least one selected from the group consisting of metal materials capable of alloying with lithium. By containing a metal material capable of alloying with lithium in the negative electrode intermediate layer, lithium metal can be more uniformly precipitated on the surface of the collector. As a specific example of a metal material capable of alloying with lithium, for example, indium (In), aluminum (Al), silicon (Si), tin (Sn), magnesium (Mg), gold (Au), silver (Ag), zinc (Zn) and alloys containing at least one of them can be cited. Among them, the metal material preferably includes at least one selected from the group consisting of In, Al, Si, Sn, Mg, Au, Ag and Zn, more preferably includes at least one selected from the group consisting of Ag, Mg, Zn and Al, further preferably includes at least one selected from the group consisting of Ag, Mg and Zn, and particularly preferably includes Ag.

[0021] The negative electrode intermediate layer preferably contains at least one selected from the group consisting of carbon materials capable of absorbing lithium ions instead of at least one selected from the group consisting of metal materials capable of alloying with lithium, or, in addition to containing at least one selected from the group consisting of metal materials capable of alloying with lithium, it also contains at least one selected from the group consisting of carbon materials capable of absorbing lithium ions. By containing a carbon material capable of absorbing lithium ions in the negative electrode intermediate layer, the precipitation and growth of lithium dendrites can be suppressed. As specific examples of carbon materials capable of absorbing lithium ions, carbon black (specifically, acetylene black, Ketjen black (registered trademark), furnace black, channel black, thermal crack lamp black, etc.), carbon nanotubes (CNT), graphite, hard carbon, etc. can be cited. Among them, the carbon material preferably includes at least one selected from the group consisting of carbon black, and more preferably at least one selected from the group consisting of acetylene black, Ketjen black (registered trademark), furnace black, channel black and thermal crack lamp black.

[0022] In addition, the negative electrode intermediate layer may further include a metal material other than the above-mentioned metal material capable of alloying with lithium (a metal material not alloyed with lithium) in addition to at least one selected from the group consisting of a metal material capable of alloying with lithium and a carbon material capable of absorbing lithium ions. As metal materials not alloyed with lithium, nickel (Ni), copper (Cu), etc. can be cited. According to one embodiment, the negative electrode intermediate layer includes at least one selected from the group consisting of a carbon material capable of absorbing lithium ions and a metal material not alloyed with lithium.

[0023] According to a preferred embodiment, the negative electrode intermediate layer comprises: at least one metal particle containing a metal material capable of alloying with lithium and / or at least one carbon particle containing a carbon material capable of absorbing lithium ions. As a result, it is easy to control the porosity of the negative electrode intermediate layer to a specified value. In addition, the effect of the present invention can be obtained more significantly. According to a preferred embodiment, the negative electrode intermediate layer comprises: at least one metal particle containing a metal material capable of alloying with lithium and at least one carbon particle containing a carbon material capable of absorbing lithium ions. By using both metal particles and carbon particles to form the negative electrode intermediate layer, an all-solid-state battery with better resistance during charging, cycle characteristics and short circuit rate during charging can be obtained.

[0024] The average primary particle size of the metal particles is, for example, less than 500 nm, preferably less than 300 nm, more preferably less than 200 nm, further more preferably less than 100 nm, and particularly preferably less than 80 nm. The lower limit of the average primary particle size of the metal particles is not particularly limited, for example, more than 10 nm, preferably more than 20 nm, further preferably more than 30 nm, and further preferably more than 40 nm. In addition, the average primary particle size of the carbon particles is, for example, less than 200 nm, preferably less than 150 nm, more preferably less than 100 nm, further more preferably less than 80 nm, further more preferably less than 60 nm, further more preferably less than 50 nm, and particularly preferably less than 45 nm. The lower limit of the average primary particle size of the carbon particles is not particularly limited, for example, more than 10 nm, preferably more than 20 nm, and further preferably more than 25 nm. If the average primary particle size of the metal particles and the average primary particle size of the carbon particles are within the above range, it is easy to control the porosity in the negative electrode intermediate layer described later within the specified range. It should be noted that, in this specification, the average primary particle size of the particles refers to the 50% cumulative diameter (D50) of the particle size (the maximum distance between any two points on the contour line of the observed particle) observed in several to dozens of fields of view when observing the cross-section of the layer containing the particles using a scanning electron microscope (SEM).

[0025] When both carbon particles and metal particles are used, the mass ratio of carbon particles to metal particles (carbon particles: metal particles) is preferably 10:1 to 1:1, more preferably 5:1 to 2:1, and further preferably 4:1 to 2.5:1. As the volume ratio of carbon particles to metal particles (carbon particles: metal particles), it is preferably 99:1 to 70:30, and more preferably 95:5 to 75:25. If the mixing ratio (mass ratio or volume ratio) of carbon particles to metal particles is within the above range, an all-solid-state battery with better resistance, cycle characteristics and short circuit rate during charging can be obtained. In addition, metal particles sometimes change their volume significantly (expand) due to alloying with lithium. Therefore, when both carbon particles and metal particles are used, it is preferred that the ratio of the mass of carbon particles contained in the negative electrode intermediate layer to the mass of metal particles (mass of carbon particles / mass of metal particles) exceeds 1. As a result, it is easy to maintain the specified porosity, and an all-solid-state battery with better cycle characteristics and short circuit rate during charging can be obtained.

[0026] From the same viewpoint, the average primary particle size of carbon particles is preferably smaller than the average primary particle size of metal particles. The ratio of the average primary particle size of carbon atoms to the average primary particle size of metal particles (the average primary particle size of carbon particles / the average primary particle size of metal particles) is preferably less than 1, more preferably less than 0.9, more preferably less than 0.8, and further more preferably less than 0.7. Thus, it is easy to maintain a specified porosity, and it is possible to obtain a more excellent all-solid-state battery with cycle characteristics and short circuit rate during charging. In addition, from the viewpoint of easily controlling the porosity within a specified range, the ratio of the primary particle size of carbon particles to the average primary particle size of metal particles is, for example, more than 0.3, more preferably more than 0.4, and more preferably more than 0.5.

[0027] According to a preferred embodiment, the ratio of the mass of the carbon particles contained in the negative electrode intermediate layer to the mass of the metal particles (the mass of the carbon particles / the mass of the metal particles) exceeds 1, and the ratio of the average primary particle size of the carbon atoms to the average primary particle size of the metal particles (the average primary particle size of the carbon particles / the average primary particle size of the metal particles) is less than 1. Thus, it is easy to maintain the specified porosity, and an all-solid-state battery with better cycle characteristics and short-circuit rate during charging can be obtained.

[0028] The negative electrode intermediate layer also includes a binder. The type of binder is not particularly limited, and a binder known in the art can be appropriately used. As an example of a binder, polyvinylidene fluoride (PVDF), a compound in which hydrogen atoms of PVDF are replaced by other halogen elements, polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) can be cited. Among them, from the viewpoint of easily controlling the porosity and thickness of the negative electrode intermediate layer described later within a specified range, the binder preferably includes polyvinylidene fluoride (PVDF), and more preferably polyvinylidene fluoride (PVDF).

[0029] The content of the binder in the negative electrode intermediate layer is, for example, 8% by mass or more, preferably 10% by mass or more, and more preferably 12% by mass or more, relative to the total mass of the metal material (e.g., metal particles), the carbon material (e.g., carbon particles), and the binder, 100% by mass. If the content of the binder is within the above range, it is easy to control the porosity in the negative electrode intermediate layer described later within a specified range. The upper limit of the content of the binder is not particularly limited. From the perspective of suppressing the increase in resistance, it is preferably 20% by mass or less, more preferably 18% by mass or less, and further preferably 16% by mass or less.

[0030] The ratio of the total surface area of ​​the at least one metal particle containing the metal material capable of alloying with lithium and the at least one carbon particle containing the carbon material capable of absorbing lithium ions contained in the negative electrode intermediate layer to the mass of the binder (total surface area of ​​the metal particles and the carbon particles / mass of the binder) is 800 m 2 / g or less. If the value of the above (total surface area of ​​metal particles and carbon particles / mass of binder) is 800m 2 / g or less, there is a sufficient amount of binder on the surface of the metal particles and carbon particles, so the bonding force between these particles is improved. As a result, it is easy to reduce the porosity of the negative electrode intermediate layer and control the porosity of the negative electrode intermediate layer within the range of 10% to 70%. The above value (total surface area of ​​metal particles and carbon particles / mass of binder) is more preferably 700m 2 / g or less, more preferably 600m 2 / g or less, and more preferably 500m 2 / g or less, particularly preferably 450m 2 / g or less. In addition, the value of the above (total surface area of ​​metal particles and carbon particles / mass of binder) is, for example, 10 m 2 / g or more, preferably 100m 2 / g or more, more preferably 200m 2 / g or more, more preferably 300m / g 2 / g or more. If it is within the above range, the energy density of the all-solid-state battery can be improved. It should be noted that the value of the above (total surface area of ​​metal particles and carbon particles / mass of binder) is calculated as follows: according to the type of particles, the volume of each particle is calculated in the form of spherical particles with a radius of its average primary particle size / 2. According to the mixing ratio of each component contained in the negative electrode intermediate layer, the number of particles contained in the unit mass of the negative electrode intermediate layer is calculated, and the surface area of ​​each particle of the above spherical particles is calculated and multiplied therewith to obtain the total surface area of ​​each particle. Moreover, the total surface area of ​​each type of each particle is added as the total surface area, and it is divided by the mass of the binder contained in the unit mass of the negative electrode intermediate layer to obtain the above (total surface area of ​​metal particles and carbon particles / mass of binder). Specifically, it can be obtained by the method described in the embodiments described later.

[0031] In a preferred embodiment, the average primary particle size of the metal particles or carbon particles contained in the negative electrode intermediate layer is 30 nm or more, and the content of the binder may be 10 parts by mass or more relative to 100 parts by mass of the total of the metal particles, carbon particles and the binder.

[0032] It should be noted that, when the negative electrode intermediate layer contains the above-mentioned metal particles and does not contain the above-mentioned carbon particles, the above-mentioned (total surface area of ​​the metal particles and the carbon particles / mass of the binder) refers to (total surface area of ​​the metal particles / mass of the binder). Similarly, when the negative electrode intermediate layer contains the above-mentioned carbon particles and does not contain the above-mentioned metal particles, the above-mentioned (total surface area of ​​the metal particles and the carbon particles / mass of the binder) refers to (total surface area of ​​the carbon particles / mass of the binder).

[0033] The ratio of the total mass of the metal material, carbon material and binder to the total mass of the negative electrode intermediate layer is preferably 90 mass % or more, more preferably 95 mass % or more, further preferably 98 mass % or more, particularly preferably 99 mass % or more, and most preferably 100 mass %.

[0034] The all-solid-state battery of this method is characterized in that the porosity of the negative electrode intermediate layer is greater than 10% and less than 70%. In a lithium precipitation type all-solid-state battery, lithium ions are supplied from the positive electrode side during charging, and lithium metal is precipitated between the negative electrode collector and the negative electrode intermediate layer to form a negative electrode active material layer, but sometimes lithium metal is also precipitated in the pores of the negative electrode intermediate layer and partially contacts the solid electrolyte layer. If the porosity of the negative electrode intermediate layer exceeds 70%, lithium metal is easily precipitated in the pores of the negative electrode intermediate layer, and the lithium metal precipitated in the pores of the negative electrode active material layer is more likely to contact the solid electrolyte layer. As a result, the precipitated lithium metal grows through the pores in the solid electrolyte layer and contacts the positive electrode active material layer, which sometimes causes a short circuit in the battery.

[0035] In addition, if the porosity of the negative electrode intermediate layer exceeds 70%, the solid electrolyte contained in the solid electrolyte layer enters the vicinity of the negative electrode active material layer (lithium metal precipitated on the negative electrode collector), and the solid electrolyte may be degraded by reduction decomposition due to the precipitated lithium metal. Furthermore, if the porosity of the negative electrode intermediate layer exceeds 70%, the strength of the negative electrode intermediate layer may decrease. As a result, as the battery is charged and discharged, the precipitation and disappearance of lithium metal are repeated, and the structure of the negative electrode intermediate layer is destroyed by the stress generated by the lithium metal during precipitation, and the conductive path may be destroyed. In addition, as the battery is charged and discharged, the strength is further reduced, and the negative electrode intermediate layer may be broken. As a result, even if a short circuit does not occur, the cycle durability of the battery is sometimes reduced. In addition, since the contact area between the negative electrode intermediate layer and the solid electrolyte layer is small, the resistance sometimes increases during charging.

[0036] On the other hand, if the porosity of the negative electrode intermediate layer is less than 10%, the current density during charging becomes high, thereby promoting the generation of lithium dendrites and possibly causing a short circuit. In addition, even if a short circuit does not occur, the battery resistance during charging may increase due to the high current density during charging.

[0037] The porosity of the negative electrode intermediate layer is preferably less than 65%, more preferably less than 60%, and further preferably less than 55%. In addition, the porosity of the negative electrode intermediate layer is preferably more than 15%, more preferably more than 20%, and further preferably more than 25%. According to a preferred embodiment of the present invention, the porosity of the negative electrode intermediate layer is more than 10% and less than 60%. As a result, the resistance during charging and the cycle durability can be further improved. According to a more preferred embodiment of the present invention, the porosity of the negative electrode intermediate layer is more than 20% and less than 60%. As a result, the resistance during charging and the cycle durability can be further improved. It should be noted that in this specification, the porosity of the negative electrode intermediate layer adopts the value measured by the method described in the embodiments described later.

[0038] There is no particular limitation on the method for controlling the porosity of the negative electrode intermediate layer within a specified range. When manufacturing an all-solid-state battery, the following method can be used: after the solid electrolyte layer is pressed at a specified pressure, a two-stage pressing process is performed such that the solid electrolyte layer is stacked with the negative electrode intermediate layer and pressed at a specified pressure. In more detail, a solid electrolyte slurry containing a solid electrolyte is applied to the surface of a support (such as a metal foil), and the coating is dried to obtain a solid electrolyte layer formed on the surface of the support. Then, the solid electrolyte layer formed on the surface of the support is pressed at a specified pressure (first pressing process). Thus, the arrangement of the solid electrolyte particles on the surface adjacent to the support in the solid electrolyte layer is arranged to reduce the unevenness. It should be noted that it is also possible to use other metal foils, etc. for pressing after the support used in the film formation of the solid electrolyte layer is peeled off. In addition, it is also possible to configure the exposed surface of the positive electrode active material layer prepared separately on the exposed surface of the solid electrolyte layer before the first pressing process, and perform the first pressing process in a state where the solid electrolyte layer and the positive electrode active material layer are overlapped. That is, according to a preferred embodiment of the present invention, the exposed surface of the positive electrode active material layer prepared separately is arranged on the exposed surface of the solid electrolyte layer before the first pressing process, and the first pressing process is performed in a state where the solid electrolyte layer and the positive electrode active material layer are overlapped. On the other hand, the negative electrode intermediate layer slurry containing the material (metal particles and / or carbon particles and binder) contained in the negative electrode intermediate layer is applied to the surface of the negative electrode collector (such as stainless steel foil), and the coating is dried to obtain a negative electrode intermediate layer formed on the surface of the negative electrode collector. Then, the support (metal foil) used in the first pressing process is peeled off to expose the solid electrolyte layer, and the exposed surface of the solid electrolyte layer is overlapped with the exposed surface of the negative electrode intermediate layer in a manner relative to each other, and pressed at a specified pressure (second pressing process). At this time, the porosity of the negative electrode intermediate layer can be adjusted by adjusting the pressing pressure, pressing temperature, and pressing time of the second pressing process. At this time, the porosity of the negative electrode intermediate layer can be more appropriately adjusted by further adjusting the compounding amount of the metal particles and / or carbon particles contained in the negative electrode intermediate layer and their average primary particle size, as well as the compounding amount of the binder. Specifically, as described above, if the ratio of the total surface area of ​​the metal particles and carbon particles contained in the negative electrode intermediate layer to the mass of the binder is adjusted to 800 m 2 / g or less, the porosity can be easily controlled within a specified range. Furthermore, even after the pressing pressure is released, the porosity achieved by the pressing process can be maintained, so it is preferred. It should be noted that cold isostatic pressing (CIP) is suitable for the pressing of the first pressing process and the second pressing process, but is not limited thereto.

[0039] In the above manufacturing method, it is preferred that the negative electrode intermediate layer alone is not pressed before the second pressing step because if only the negative electrode intermediate layer is pressed, the porosity of the negative electrode intermediate layer may become lower than a predetermined value.

[0040] The pressing pressure of the first pressing process varies according to the material contained in the solid electrolyte layer. When the first pressing process is performed in a state where the solid electrolyte layer and the positive electrode active material layer are overlapped, it varies according to the materials contained in the solid electrolyte layer and the positive electrode active material layer, and can be appropriately set by a person skilled in the art. If an example is given, the pressing pressure of the first pressing process is preferably 300 MPa or more and 1000 MPa or less, more preferably 300 MPa or more and 800 MPa or less, and further preferably 500 MPa or more and 700 MPa or less. The pressing temperature of the first pressing process is not particularly limited, for example, 20°C to 80°C, preferably 20°C to 40°C. The pressing time of the first pressing process is also not particularly limited, for example, 10 seconds to 30 minutes, preferably 10 seconds to 10 minutes.

[0041] The pressing pressure of the second pressing process varies according to the material contained in the negative electrode intermediate layer and the desired porosity, and can be appropriately set by those skilled in the art. If an example is given, the pressing pressure of the second pressing process is preferably 100 MPa or more and 700 MPa or less, more preferably 300 MPa or more and 700 MPa or less, and further preferably 500 MPa or more and 700 MPa or less. When it is the above range, the porosity of the negative electrode intermediate layer can be easily controlled to a specified value.

[0042] The pressing temperature of the second pressing step varies according to the material contained in the negative electrode intermediate layer and the desired porosity, and can be appropriately set by a person skilled in the art. For example, the pressing temperature of the second pressing step is preferably 20°C to 90°C, and more preferably 25°C to 80°C. When it is in the above range, the porosity of the negative electrode intermediate layer can be easily controlled to a specified value.

[0043] The pressing time of the second pressing process varies according to the material contained in the negative electrode intermediate layer and the desired porosity, and can be appropriately set by a person skilled in the art. For example, the pressing time of the second pressing process is preferably 10 seconds to 30 minutes, and more preferably 1 to 10 minutes. When it is within the above range, the porosity of the negative electrode intermediate layer can be more easily controlled to a specified value.

[0044] The thickness of the negative electrode intermediate layer is not particularly limited, and is preferably less than 10 μm, more preferably less than 7 μm, and further preferably less than 6 μm. If the thickness of the negative electrode intermediate layer is less than 10 μm, the path of lithium ions moving in the negative electrode intermediate layer during charging will not become too long, so the resistance during charging can be suppressed to a low level. In addition, the energy density of the all-solid-state battery can be improved. There is no particular restriction on the lower limit of the thickness of the negative electrode intermediate layer. From the perspective of ensuring the strength of the negative electrode intermediate layer, it is, for example, more than 1 μm, preferably more than 1.5 μm, and more preferably more than 2 μm. It should be noted that in this specification, the thickness of the negative electrode intermediate layer adopts the value measured by the method described in the embodiments described later.

[0045] [Solid electrolyte layer]

[0046] The solid electrolyte layer is located between the negative electrode and the positive electrode, and contains a solid electrolyte (usually as the main component). The solid electrolyte contained in the solid electrolyte layer is not particularly limited, and solid electrolytes known in the technical field can be appropriately used, such as sulfide solid electrolytes and oxide solid electrolytes. From the perspective of showing excellent lithium ion conductivity, the solid electrolyte is preferably a sulfide solid electrolyte containing the S element, more preferably a sulfide solid electrolyte containing the Li element, the M element and the S element, and the above-mentioned M element contains at least one element selected from the group consisting of P, Si, Ge, Sn, Ti, Zr, Nb, Al, Sb, Br, Cl and I, and further preferably a sulfide solid electrolyte containing the S element, the Li element and the P element. As an example, LPS (Li 2 SP 2 S 5 )、Li 6 PS 5 X (wherein X is Cl, Br or I), Li 7 P 3 S 11 , Li 3.2 P 0.96 S and Li 3 PS 4 These sulfide solid electrolytes have excellent lithium ion conductivity and are therefore preferably used.

[0047] The ion conductivity (for example, Li ion conductivity) of the solid electrolyte (for example, sulfide solid electrolyte) at room temperature (25° C.) is preferably 1×10 -5 S / cm or more, more preferably 1×10 -4 S / cm or more. It should be noted that the value of the ion conductivity of the solid electrolyte can be measured by an alternating current impedance method.

[0048] As the shape of the solid electrolyte, for example, there can be granular shapes such as a true sphere and an ellipsoid, a thin film, etc. When the solid electrolyte is granular, its average particle size (D50) is not particularly limited, and is preferably 0.01 μm or more and 40 μm or less, more preferably 0.1 μm or more and 20 μm or less, and further preferably 0.5 μm or more and 10 μm or less.

[0049] The content of the solid electrolyte in the solid electrolyte layer is preferably 50% by mass to 100% by mass, and more preferably 90% by mass to 100% by mass.

[0050] The solid electrolyte layer may contain a binder in addition to the solid electrolyte. The binder is not particularly limited, and a known binder may be used appropriately, for example, the binder described in the above-mentioned negative electrode intermediate layer may be used in the same manner. The content of the binder in the solid electrolyte layer is not particularly limited, for example, 1 mass % to 10 mass %.

[0051] The thickness of the solid electrolyte layer varies depending on the configuration of the intended all-solid-state battery, but is generally 0.1 to 1000 μm, preferably 10 to 100 μm.

[0052] [Positive electrode active material layer]

[0053] The positive electrode active material layer necessarily contains a positive electrode active material, and may contain a solid electrolyte, a binder, and a conductive aid as necessary.

[0054] The type of the positive electrode active material contained in the positive electrode active material layer is not particularly limited, and examples thereof include LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 、Li(Ni-Mn-Co)O 2 Layered rock salt type active material, LiMn 2 O 4 、LiNi 0.5 Mn 1.5 O 4 Spinel active materials, LiFePO 4 、LiMnPO 4 Olivine-type active materials, Li 2 FeSiO 4 , Li 2 MnSiO 4 Other oxide active materials other than those mentioned above include Li 4 Ti 5 O 12 Among them, Li(Ni-Mn-Co)O is preferably used.2 A material in which a part of these transition metals is replaced by other elements (hereinafter also referred to as "NMC composite oxide") is used as a positive electrode active material.

[0055] In addition, the use of a sulfur-based positive electrode active material is also one of the preferred embodiments. Examples of the sulfur-based positive electrode active material include particles or films of organic sulfur compounds or inorganic sulfur compounds, as long as they can release lithium ions during charging and absorb lithium ions during discharge by utilizing the redox reaction of sulfur.

[0056] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is, for example, preferably 30 to 99 mass %, more preferably 40 to 90 mass %, and further preferably 45 to 80 mass %.

[0057] The positive electrode active material layer preferably further includes a solid electrolyte. As a specific form of the solid electrolyte contained in the positive electrode active material layer, the form described in the column of the solid electrolyte layer can be similarly adopted. Since it has excellent lithium ion conductivity and a low bulk modulus, it can be followed by the volume change of the positive electrode active material accompanying charge and discharge, so it is preferred to use a sulfide solid electrolyte. There is no particular restriction on the content of the solid electrolyte in the positive electrode active material layer, for example, 1 to 70% by mass, preferably 10 to 60% by mass, and more preferably 20 to 55% by mass.

[0058] The binder used in the positive electrode active material layer is not particularly limited, and a known binder can be used appropriately. For example, the binder described in the above-mentioned negative electrode intermediate layer can be used. The content of the binder in the positive electrode active material layer is not particularly limited, and is, for example, 1 mass % to 10 mass %.

[0059] There is no particular limitation on the conductive aid used in the positive electrode active material layer, and for example, carbon black (specifically, acetylene black, Ketjen black (registered trademark), furnace black, channel black, thermal lamp black, etc.) and other carbons can be used. The content of the conductive aid in the positive electrode active material layer is not particularly limited, and is, for example, 10% to 30% by mass.

[0060] The thickness of the positive electrode active material layer varies depending on the structure of the target all-solid-state battery, but is usually 0.1 to 1000 μm, preferably 10 to 300 μm.

[0061] As mentioned above, one embodiment of the all-solid-state battery of the present invention has been described. However, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.

[0062] The present invention includes the following modes and aspects:

[0063] 1. An all-solid-state battery comprising a power generation element, wherein the power generation element has:

[0064] a positive electrode having a positive electrode active material layer containing a positive electrode active material;

[0065] A negative electrode having a negative electrode current collector, and lithium metal is deposited on the negative electrode current collector during charging;

[0066] a solid electrolyte layer interposed between the positive electrode and the negative electrode and containing a solid electrolyte; and

[0067] a negative electrode intermediate layer which exists adjacent to the surface of the solid electrolyte layer on the negative electrode collector side and contains at least one selected from the group consisting of a metal material capable of alloying with lithium and a carbon material capable of absorbing lithium ions, and a binder,

[0068] The porosity of the negative electrode intermediate layer is greater than 10% and less than 70%;

[0069] 2. The all-solid-state battery according to 1. above, wherein the porosity of the negative electrode intermediate layer is greater than 10% and less than 60%;

[0070] 3. The all-solid-state battery according to 1. or 2. above, wherein the porosity of the negative electrode intermediate layer is greater than or equal to 20% and less than or equal to 60%;

[0071] 4. The all-solid-state battery according to any one of 1. to 3. above, wherein the thickness of the negative electrode intermediate layer is 10 μm or less;

[0072] 5. The all-solid-state battery according to any one of 1. to 4. above, wherein the negative electrode intermediate layer comprises: at least one metal particle containing a metal material capable of alloying with lithium and / or at least one carbon particle containing a carbon material capable of absorbing lithium ions;

[0073] 6. The all-solid-state battery according to any one of 1. to 5. above, wherein the negative electrode intermediate layer comprises: at least one metal particle containing a metal material capable of alloying with lithium and at least one carbon particle containing a carbon material capable of absorbing lithium ions;

[0074] 7. The all-solid-state battery according to 5. or 6. above, wherein the ratio of the total surface area of ​​the at least one metal particle containing a metal material capable of alloying with lithium and the at least one carbon particle containing a carbon material capable of absorbing lithium ions contained in the negative electrode intermediate layer to the mass of the binder is 800 m 2 / g or less.

[0075] Example

[0076] The present invention is described in more detail below by way of examples. However, the technical scope of the present invention is not limited to the following examples. It should be noted that the following operations are performed in a glove box. In addition, the apparatus and devices used in the glove box are fully dried in advance.

[0077] <Production Example of Evaluation Battery>

[0078] [Example 1]

[0079] (Production of positive electrode)

[0080] First, as a constituent material of the positive electrode active material layer, an NMC composite oxide (composition = LiNi 0.8 Mn 0.1 Co 0.1 O 2 ), Argentum-type sulfide solid electrolyte (Li 6 PS 5 Cl), acetylene black as a conductive aid, and styrene-butadiene rubber (SBR) as a binder.

[0081] Among these, NMC composite oxide, solid electrolyte and acetylene black were weighed in a mass ratio of 50:30:20, mixed with an agate mortar in a glove box, and further mixed and stirred with a planetary ball mill. 2 parts by mass of styrene-butadiene rubber (SBR) was added to 100 parts by mass of the obtained mixed powder, and xylene was added as a solvent to prepare a positive electrode active material slurry. Next, the prepared positive electrode active material slurry was applied to the surface of the carbon-coated aluminum foil as the positive electrode collector and dried to form a positive electrode active material layer (thickness 200 μm) to make a positive electrode.

[0082] (Fabrication of Solid Electrolyte Layer)

[0083] In a glove box with an argon atmosphere at a dew point below -68°C, a solid electrolyte of argon-germanite type sulfide solid electrolyte (Li 6 PS 5 Cl) and SBR as a binder are mixed in a mass ratio of 95:5, and an appropriate amount of xylene is added as a solvent and mixed to prepare a solid electrolyte slurry. The solid electrolyte slurry is applied to one surface of a stainless steel foil as a support and dried to obtain a solid electrolyte layer (thickness 80 μm).

[0084] (Fabrication of negative electrode intermediate layer)

[0085] Acetylene black (average primary particle size (D50): 35 nm) and silver nanoparticles (average primary particle size (D50): 60 nm) were weighed and mixed in a mass ratio of acetylene black (AB): Ag = 3: 1. 14 parts by mass of polyvinylidene fluoride (PVDF) as a binder was added to 86 parts by mass of the obtained mixture, and N-methylpyrrolidone was added as a solvent and mixed to prepare a negative electrode intermediate layer slurry. The negative electrode intermediate layer slurry was applied to the surface of a stainless steel foil as a negative electrode collector and dried to obtain a negative electrode intermediate layer (thickness before pressing: 10 μm).

[0086] (Production of Evaluation Batteries)

[0087] The positive electrode active material layer formed on the surface of the aluminum foil (positive electrode collector) and the solid electrolyte layer formed on the surface of the stainless steel foil are overlapped in a manner that the exposed surface of the positive electrode active material layer faces the exposed surface of the solid electrolyte layer, and are pressed by cold isostatic pressing (CIP) at 700 MPa and 25°C for 1 minute (first pressing step). After the stainless steel foil adjacent to the solid electrolyte layer is peeled off, the solid electrolyte layer and the negative electrode intermediate layer formed on the surface of the stainless steel foil (negative electrode collector) are overlapped in a manner that the exposed surface of the solid electrolyte layer faces the exposed surface of the negative electrode intermediate layer, and are pressed by cold isostatic pressing (CIP) at 500 MPa and 80°C for 1 minute (second pressing step). As a result, the negative electrode intermediate layer is transferred to the exposed surface of the solid electrolyte layer, and the porosity of the negative electrode intermediate layer is adjusted. Finally, the aluminum positive electrode tab and the nickel negative electrode tab are joined on the aluminum foil (positive electrode collector) and the stainless steel foil (negative electrode collector) respectively using an ultrasonic welding machine, and the obtained stack is placed inside an aluminum laminate film and vacuum-sealed, thereby obtaining a battery for evaluation of the lithium precipitation-type all-solid-state battery of this embodiment.

[0088] [Example 2]

[0089] In the above (Production of Evaluation Battery), an evaluation battery of this example was produced in the same manner as in Example 1 except that the pressing temperature in the second pressing step was changed to 25°C.

[0090] [Example 3]

[0091] In the above (Production of Evaluation Battery), an evaluation battery of this example was produced in the same manner as in Example 1 except that the pressing pressure in the second pressing step was changed to 700 MPa and the pressing temperature was changed to 25°C.

[0092] [Example 4]

[0093] In the above (Production of Evaluation Battery), an evaluation battery of this example was produced in the same manner as in Example 1 except that the pressing pressure in the second pressing step was changed to 700 MPa and the pressing time was changed to 10 minutes.

[0094] [Example 5]

[0095] In the above (Production of Evaluation Battery), an evaluation battery of this example was produced in the same manner as in Example 1 except that the pressing pressure in the second pressing step was changed to 100 MPa and the pressing temperature was changed to 25°C.

[0096] [Comparative Example 1]

[0097] In the above (production of evaluation batteries), after the first pressing step and before the second pressing step, the negative electrode intermediate layer formed on the surface of the stainless steel foil (negative electrode collector) was roll-pressed at a linear pressure of 3.0 kN / cm at 25°C, and the pressing pressure of the second pressing step was changed to 700 MPa and the pressing time was changed to 10 minutes. Except for this, the evaluation battery of this comparative example was produced by the same method as Example 1.

[0098] [Comparative Example 2]

[0099] In the above (Production of Evaluation Battery), an evaluation battery of this comparative example was produced in the same manner as in Example 1 except that the second pressing step was not performed.

[0100] [Comparative Example 3]

[0101] In the above (production of the negative electrode intermediate layer), acetylene black was changed to acetylene black having an average primary particle size (D50) of 12 nm. Moreover, 12 parts by mass of polyvinylidene fluoride (PVDF) as a binder was added to 88 parts by mass of the mixture mixed in a mass ratio of AB:Ag=3:1. In addition, in the above (production of the evaluation battery), the pressing temperature of the second pressing step was changed to 25°C and the pressing time was changed to 30 minutes. Except for the above, the evaluation battery of this comparative example was produced in the same manner as in Example 1.

[0102] [Comparative Example 4]

[0103] In the above (production of the negative electrode intermediate layer), acetylene black was changed to acetylene black having an average primary particle size (D50) of 38 nm. Moreover, 4 parts by mass of polyvinylidene fluoride (PVDF) as a binder were added to 96 parts by mass of the mixture mixed in a mass ratio of AB:Ag=3:1. In addition, in the above (production of the evaluation battery), the pressing temperature of the second pressing step was changed to 25°C and the pressing time was changed to 30 minutes. Except for the above, the evaluation battery of this comparative example was produced in the same manner as in Example 1.

[0104] [Comparative Example 5]

[0105] In the above (production of the negative electrode intermediate layer), acetylene black was changed to acetylene black having an average primary particle size (D50) of 30 nm. Moreover, 8 parts by mass of polyvinylidene fluoride (PVDF) as a binder was added to 92 parts by mass of the mixture mixed in a mass ratio of AB:Ag=3:1. In addition, in the above (production of the evaluation battery), the pressing temperature of the second pressing step was changed to 25°C and the pressing time was changed to 30 minutes. Except for the above, the evaluation battery of this comparative example was produced in the same manner as in Example 1.

[0106] <Measurement of Porosity and Thickness of Negative Electrode Intermediate Layer>

[0107] The porosity of the negative electrode intermediate layer is a value calculated from the negative electrode intermediate layer in a state after discharge in which the battery is fully discharged and the outer casing is removed, and can be calculated using “3D-SEM”.

[0108] Specifically, the power generation element is taken out from the evaluation battery after full discharge, and the cross section (stacked cross section) perpendicular to the surface direction is exposed by ion milling. A focused ion beam processing-scanning electron microscope (FIB-SEM) manufactured by Hitachi High-Tech Science Corporation is used to take a SEM photograph of the stacked cross section of the power generation element observed from the front, that is, a photograph of the surface portion of the negative electrode intermediate layer (a photograph of 5μm×5μm size). Then, the surface of the negative electrode intermediate layer is irradiated with an ion beam, the surface of the negative electrode intermediate layer is excavated, and a photograph of the surface of the negative electrode intermediate layer is taken again. The excavation of the surface of the negative electrode intermediate layer and the photographing of the surface of the negative electrode intermediate layer by the above-mentioned ion beam irradiation are repeated to obtain a group of 2D photographs of the surface of the negative electrode intermediate layer. Then, the 2D regions of each of the obtained set of 2D photographs are identified, the area of ​​the pores existing in the 2D region is calculated, and the volume of the pores in the 3D region is calculated by integrating the area. Then, the pore volume relative to the overall volume of the 3D region is calculated, thereby calculating the porosity.

[0109] It should be noted that the lithium metal in the negative electrode intermediate layer is set as a pore. Specifically, in the case where lithium metal remains in the pores in the evaluation battery after discharge, the lithium metal is used as the pore and the area is calculated. Regarding the determination of lithium metal, the lithium metal is determined by high-sensitivity EDS, and the lithium metal is determined by the contrast of the determined lithium metal to calculate its area.

[0110] Furthermore, the cross section is observed using a SEM, and the thickness is measured at several to several dozen different locations in the negative electrode intermediate layer, and the arithmetic average of these measurements is taken as the thickness of the negative electrode intermediate layer.

[0111] It should be noted that in this embodiment, for the evaluation battery after the charge and discharge test described later, the porosity and thickness of the negative electrode intermediate layer are measured after full discharge, but for the evaluation battery before the first charge, the same values ​​of the porosity and thickness of the negative electrode intermediate layer are also obtained.

[0112] <Ratio of the total surface area of ​​the silver nanoparticles and acetylene black particles contained in the negative electrode intermediate layer to the mass of the binder>

[0113] The ratio (m2) of the total surface area of ​​the silver nanoparticles and acetylene black particles contained in the negative electrode intermediate layer to the mass of the binder was determined by the following procedure. 2 / g).

[0114] (1) understanding the mass of acetylene black particles, silver nanoparticles, and binder per unit mass of the negative electrode intermediate layer, and their specific gravity,

[0115] (2) Understand the average primary particle size of acetylene black particles and the average primary particle size of silver nanoparticles,

[0116] (3) According to (1) and (2) above, each particle is made into a spherical shape, and the number of acetylene black particles and the number of silver nanoparticles per unit mass of the negative electrode intermediate layer are calculated. Then, using 4πr 2 × the number of particles (r is the average primary particle size of acetylene black particles or silver nanoparticles / 2), the total surface area of ​​acetylene black particles and the total surface area of ​​silver nanoparticles are calculated and added, and then divided by the mass of the binder per unit mass of the negative electrode intermediate layer.

[0117] Here, the specific gravity of acetylene black particles, silver nanoparticles, and binder is set to 2.01 g / cm 3 , 11.23g / cm 3 , and 1.89g / cm 3 The results are shown in Table 1 below.

[0118] <Evaluation of the presence or absence of short circuit>

[0119] The positive electrode collector and the negative electrode collector of the evaluation battery (before the first charge) prepared above were connected with a positive lead and a negative electrode lead, respectively. A pressure member was used to apply a restraining pressure of 3 MPa in the stacking direction of the evaluation battery, and a charging process was carried out at a charging rate of 0.5 C from SOC0% inside a constant temperature chamber at 60°C to investigate the presence or absence of a short circuit in the evaluation battery within 30 minutes. It should be noted that when the voltage of the evaluation battery drops in the middle of the charging process, it is judged that a short circuit has occurred. In addition, the evaluation battery judged to have a short circuit was disassembled and the inside of the battery was observed, and the formation of dendrites formed by lithium metal was confirmed. The results are shown in the following Table 1.

[0120] <Cyclic test>

[0121] The positive electrode collector and the negative electrode collector of the evaluation battery (before the first charge) prepared as above were connected with a positive electrode lead and a negative electrode lead, respectively, and a cycle test was performed while applying a constraint pressure of 3 MPa in the stacking direction of the evaluation battery using a pressurizing component. In the cycle test, the charge and discharge at a charge and discharge rate of 0.5C (charging CCCV mode (0.01C cutoff), discharging CC mode) was repeated 200 times at 60°C and a battery voltage range of 3.0V to 4.3V to perform the cycle test. In addition, the ratio of the 200th discharge capacity to the first discharge capacity was determined as the discharge capacity retention rate (capacity retention rate) (%). The results are shown in Table 1 below. In addition, the discharge capacity retention rate of the evaluation batteries of Comparative Examples 1 and 2 could not be measured due to short circuits.

[0122] <Measurement of resistance during charging>

[0123] The positive electrode collector and the negative electrode collector of the evaluation battery (before the first charge) prepared as described above are connected with a positive lead and a negative electrode lead, respectively, and a pressure member is used to apply a restraining pressure of 3 MPa in the stacking direction of the evaluation battery while charging to SOC = 50%. Then, charging is repeated in the order of (1) to (7) below, and the relationship between the current amount and the voltage rise is plotted. The resistance during charging is calculated from the slope of the plotted graph. It should be noted that the following (1) to (7) are all carried out at a temperature of 60°C. The value of the resistance during charging of each evaluation battery is shown in the following Table 1 as a relative value when the resistance during charging of the evaluation battery of Example 1 is set to 100. In addition, the batteries of Comparative Examples 1 and 2 could not measure the resistance during charging due to short circuits.

[0124] (1) 0.05C CC charging for 15 seconds

[0125] (2) Rest for 2 hours

[0126] (3) 0.1C CC charging for 15 seconds

[0127] (4) Rest for 2 hours

[0128] (5) 0.2C CC charging for 15 seconds

[0129] (6) Rest for 2 hours

[0130] (7) 0.5C CC charging for 15 seconds.

[0131] [Table 1]

[0132]

[0133] According to the results in Table 1, for the evaluation batteries of Examples 1 to 5 having a negative electrode intermediate layer containing a specified metal material (metal particles), a carbon material (carbon particles) and a binder and having a porosity of 10% to 70%, the resistance during charging, the cycle characteristics and the short circuit rate during charging are all good. In contrast, it can be seen that in the evaluation batteries of Comparative Examples 1 and 2 whose porosity of the negative electrode intermediate layer is outside the above range, a short circuit occurs during charging. In addition, in the evaluation batteries of Comparative Examples 3 to 5 whose porosity of the negative electrode intermediate layer is outside the above range, although a short circuit does not occur, a battery with low cycle durability, good performance in the resistance during charging, cycle characteristics and short circuit rate during charging cannot be obtained.

[0134] This application is based on Japanese Patent Application No. 2022-172093 filed on October 27, 2022, the disclosure of which is incorporated herein by reference in its entirety.

[0135] Description of Reference Numerals

[0136] 10a stacked secondary battery,

[0137] 11' negative electrode current collector,

[0138] 11” positive electrode collector,

[0139] 13 negative electrode active material layer,

[0140] 14 negative electrode intermediate layer,

[0141] 15 positive electrode active material layer,

[0142] 17 Solid electrolyte layer,

[0143] 19 single cell layers,

[0144] 21 Power generation element,

[0145] 25 negative electrode collector plate,

[0146] 27 positive electrode collector plate,

[0147] 29 Laminated film.

Claims

1. An all-solid-state battery comprising a power generation element, wherein the power generation element has: a positive electrode having a positive electrode active material layer containing a positive electrode active material; A negative electrode having a negative electrode current collector, and lithium metal is deposited on the negative electrode current collector during charging; a solid electrolyte layer interposed between the positive electrode and the negative electrode and containing a solid electrolyte; and a negative electrode intermediate layer which exists adjacent to the surface of the solid electrolyte layer on the negative electrode collector side and contains at least one selected from the group consisting of a metal material capable of alloying with lithium and a carbon material capable of absorbing lithium ions, and a binder, The negative electrode intermediate layer has a porosity of 10% to 70%.

2. The all-solid-state battery according to claim 1, in, The negative electrode intermediate layer has a porosity of 10% to 60%.

3. The all-solid-state battery according to claim 1, in, The negative electrode intermediate layer has a porosity of 20% or more and 60% or less.

4. The all-solid-state battery according to claim 1 or 2, in, The thickness of the negative electrode intermediate layer is less than 10 μm.

5. The all-solid-state battery according to claim 1 or 2, in, The negative electrode intermediate layer includes at least one metal particle containing a metal material capable of alloying with lithium and / or at least one carbon particle containing a carbon material capable of absorbing lithium ions.

6. The all-solid-state battery according to claim 5, in, The negative electrode intermediate layer includes at least one kind of metal particles including a metal material capable of alloying with lithium and at least one kind of carbon particles including a carbon material capable of absorbing lithium ions.

7. The all-solid-state battery according to claim 5, in, The ratio of the total surface area of ​​the at least one metal particle containing a metal material capable of alloying with lithium and the at least one carbon particle containing a carbon material capable of absorbing lithium ions contained in the negative electrode intermediate layer to the mass of the binder is 800 m 2 / g or less.

Citation Information

Patent Citations

  • All-solid-state lithium secondary battery

    JP2020191202A